Mycorrhizal biofertilizer an effective tool to manage abiotic stress in crop plants of arid and semi-arid regions - Dev, Rahul; Dayal, Devi; Singh, Traloki (Indian Farming, 2018)
Role of VAM fertilizer in alleviating abiotic stress in plants hasbeen consistently demonstrated specially on arid and semi-arid cropspecies by various workers. The proper use of VAM fertilizer in majorcrops will be a boon in managing abiotic stress and making croppingsystem sustainable/profitable in fragile ecosystem of arid and semiarid regions.